2007
DOI: 10.1007/s10499-007-9124-z
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the effect of urchin size and diet on gonad yield and quality in the sea urchin Evechinus chloroticus Valenciennes

Abstract: We compared the gonad-enhancing effects of two diets (NIWA and NIFA diets) in two size classes of sea urchins (Evechinus chloroticus): small and large urchins with a test diameter of 75.6 ± 1.2 mm and 93.8 ± 0.5 mm, weighing 174.8 ± 7.9 g and 315 ± 5.6 g, respectively. After eight weeks being fed prepared diets, urchin gonad index (GI) had significantly surpassed that of the initial and final samples of wild urchins. Urchins in the NIWA/small treatment had a larger GI than the NIFA/small and NIFA/large treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
59
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(68 citation statements)
references
References 30 publications
5
59
4
Order By: Relevance
“…3a). These results are consistent with previous studies on other urchin species around the world, which have shown that manufactured diets are more effective at increasing GI than kelp diets (de JongWestman et al 1995, Shpigel et al 2004, Musgrove 2005, James 2006, Woods et al 2008, Phillips et al 2010, Cyrus et al 2013. Artificial diets resulted in mean GI values above 10%, regardless of site, which is better than other attempts at gonad conditioning of H. erythrogramma (Sanderson et al 1996, Musgrove 2005, Senaratna et al 2005.…”
Section: In-season Gonad Conditioningsupporting
confidence: 92%
“…3a). These results are consistent with previous studies on other urchin species around the world, which have shown that manufactured diets are more effective at increasing GI than kelp diets (de JongWestman et al 1995, Shpigel et al 2004, Musgrove 2005, James 2006, Woods et al 2008, Phillips et al 2010, Cyrus et al 2013. Artificial diets resulted in mean GI values above 10%, regardless of site, which is better than other attempts at gonad conditioning of H. erythrogramma (Sanderson et al 1996, Musgrove 2005, Senaratna et al 2005.…”
Section: In-season Gonad Conditioningsupporting
confidence: 92%
“…Decrease in absolute growth rate as a function of size has been observed in other species of sea urchins (e.g. Barker et al 1998;Ebert 2001;Woods et al 2008), so perhaps the group of large urchins chosen in this study had already reached their asymptotic size. The decrease in size by large H. purpurascens fed D. pulchra may be due to nutrient resorption from several body parts, including their tests, for survival.…”
Section: Discussionsupporting
confidence: 54%
“…FAAs in E. chloroticus gonads have been grouped by Woods et al (2008) according to their general flavour-enhancing (desirable) or flavour-detracting (undesirable) characteristics for the sushi palate. Flavour-enhancing FAAs are typically sweet (glycine, alanine, proline, serine and threonine) or umami (glutamate and asparagine) tasting.…”
Section: Discussionmentioning
confidence: 99%
“…Flavour-enhancing FAAs are typically sweet (glycine, alanine, proline, serine and threonine) or umami (glutamate and asparagine) tasting. Flavour-detracting or undesirable FAAs are bitter-or sour-tasting amino acids such as valine, histidine, isoleucine, leucine, lysine, methionine, phenylalanine and tyrosine (Woods et al 2008). The distinctive seafood flavour of E. chloroticus gonads is caused by the relative concentrations of both desirable and undesirable FAAs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation